Comment on: Associations between loneliness, disease activity, and disease impact in inflammatory arthritis: a nationwide cross-sectional study among more than 12 000 patients - Ilgen, Ufuk (Rheumatology, 2025)
Dear Editor, I read the article entitled ‘Associations between loneliness, disease activity, and disease impact in inflammatory arthritis: a nationwide cross-sectional study among more than 12 000 patients’ by Vestergaard et al. [1] with interest. The authors assessed loneliness in patients with inflammatory arthritis via digital mail with a single yes/no question: ‘Are you ever alone, although you would prefer to be together with others?’ They reported an association of loneliness with disease activity and impact, and stated the single-item question as a limitation of the study because it was not validated and might not have captured the full construct of loneliness. I believe that this limitation requires further discussion since the interpretations of the study were all built on this question.
Online veröffentlicht: 18. Februar 2025
Gesehen am 07.08.2025